Rubber composition, crosslinked product thereof, and method for producing acrylic rubber

By controlling the proportion of nonionic emulsifier fixed to the acrylic rubber within a specific range, the rubber composition achieves both water resistance and tensile strength, addressing the challenges faced by existing acrylic rubber compositions.

JP7649911B1Active Publication Date: 2025-03-21DENKA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024138941
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-12-14
Filing Date
2024-08-20
Publication Date
2025-03-21
Estimated Expiration
2044-04-05

AI Technical Summary

Technical Problem

Existing acrylic rubber compositions face challenges in maintaining both water resistance and tensile strength during cutting, despite having the same content of nonionic emulsifiers.

Method used

The rubber composition includes acrylic rubber and a nonionic emulsifier, where the proportion of nonionic emulsifier fixed to the acrylic rubber is controlled within a specific range to achieve optimal water resistance and tensile strength.

Benefits of technology

This approach allows for improved water resistance, reduced toluene insoluble content, enhanced flexural fatigue resistance, and better copper damage resistance of the crosslinked acrylic rubber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649911000001
    Figure 0007649911000001
  • Figure 0007649911000002
    Figure 0007649911000002
  • Figure 0007649911000003
    Figure 0007649911000003
Patent Text Reader

Abstract

The cross-linked acrylic rubber must have both good water resistance and good tensile strength at break. [Solution] The rubber composition contains an acrylic rubber and a nonionic emulsifier, in which more than 0 mass % and 80 mass % or less of the total mass of the nonionic emulsifier is fixed to the acrylic rubber.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rubber composition, a crosslinked product thereof, and a method for producing an acrylic rubber. [Background technology]

[0002] Acrylic rubber and its crosslinked products have excellent physical properties such as heat resistance, oil resistance, and mechanical properties, and are therefore used, for example, as materials for hoses and sealing parts in the engine compartment of automobiles. For example, Patent Document 1 discloses an acrylic rubber that contains, as monomer units, an alkyl acrylate and a crosslinked monomer, and in which the content of a nonionic emulsifier in the acrylic rubber is 0.5 to 2 mass %. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2021 / 075128 Summary of the Invention [Problem to be solved by the invention]

[0004] As disclosed in Patent Document 1, studies have been conducted focusing on the content of nonionic emulsifier coexisting with acrylic rubber, but according to the studies of the present inventors, even if the content of nonionic emulsifier coexisting with acrylic rubber is the same, the water resistance and tensile strength at break of the cross-linked acrylic rubber may change, and in some cases the water resistance or tensile strength at break may deteriorate.

[0005] Therefore, one aspect of the present invention has an object to provide a cross-linked product of an acrylic rubber that has both good water resistance and good tensile strength at break. [Means for solving the problem]

[0006] The present inventors have discovered that, although nonionic emulsifiers that coexist with acrylic rubber are generally referred to as such, there may be nonionic emulsifiers that are fixed to the acrylic rubber and relatively difficult to remove, and nonionic emulsifiers that are not fixed to the acrylic rubber and relatively easy to remove.

[0007] And, even when the same total amount of nonionic emulsifier is coexisted with acrylic rubber having the same monomer composition, if there is no nonionic emulsifier fixed to the acrylic rubber (only nonionic emulsifier not fixed to the acrylic rubber is present), the tensile strength at break of the crosslinked acrylic rubber decreases, while if there is more than the necessary amount of nonionic emulsifier fixed to the acrylic rubber, the water resistance of the crosslinked acrylic rubber deteriorates. Therefore, in order to achieve both the water resistance and the tensile strength at break of the crosslinked acrylic rubber (without lowering or worsening either one) in the case where the same total amount of nonionic emulsifier is coexisted with acrylic rubber having the same monomer composition, it is important to set the ratio of the nonionic emulsifier fixed to the acrylic rubber within a specific range.

[0008] The present invention includes the following aspects. [1] A rubber composition comprising an acrylic rubber and a nonionic emulsifier, in which more than 0 mass% and 80 mass% or less of the total mass of the nonionic emulsifier is fixed to the acrylic rubber. [2] The rubber composition according to [1], wherein the total mass of the nonionic emulsifier is 5 parts by mass or less per 100 parts by mass of the total mass of the acrylic rubber. [3] The rubber composition according to [1] or [2], wherein the acrylic rubber contains at least one monomer unit selected from the group consisting of an alkyl acrylate, an alkyl methacrylate, and an alkoxyalkyl acrylate. [4] The rubber composition according to any one of [1] to [3], further comprising a crosslinking agent. [5] A crosslinked product of the rubber composition according to any one of [1] to [4]. [6] A method for producing acrylic rubber, comprising: a step of polymerizing acrylic monomers in the presence of a nonionic emulsifier to obtain a latex of an acrylic polymer; and a step of coagulating and washing the acrylic polymer to obtain an acrylic rubber, in which more than 0% by mass but not more than 70% by mass of the total mass of the nonionic emulsifier in the latex is fixed to the acrylic polymer. [7] The method for producing an acrylic rubber according to [6], wherein the total mass of the nonionic emulsifier in the latex is 6 parts by mass or less per 100 parts by mass of the total mass of the acrylic polymer. [8] The method for producing an acrylic rubber according to [6] or [7], wherein the acrylic rubber contains at least one monomer unit selected from the group consisting of an alkyl acrylate, an alkyl methacrylate, and an alkoxyalkyl acrylate. Effect of the Invention

[0009] According to one aspect of the present invention, it is possible to achieve both water resistance and tensile strength at break of a cross-linked acrylic rubber.

[0010] According to another aspect of the present invention, the toluene insoluble content of the acrylic rubber can be reduced. According to another aspect of the present invention, the flex fatigue resistance of the cross-linked product of the acrylic rubber can be improved. According to another aspect of the present invention, the copper damage resistance of the cross-linked product of the acrylic rubber can be improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] One embodiment of the present invention is a method for producing acrylic rubber, comprising a step of polymerizing acrylic monomers in the presence of a nonionic emulsifier to obtain an acrylic polymer latex (hereinafter also referred to as "step S1"), and a step of coagulating and washing the acrylic polymer to obtain an acrylic rubber (hereinafter also referred to as "step S2").

[0012] In step S1, for example, a monomer mixture containing an acrylic monomer and a polymerization initiator are added to a suspension of a nonionic emulsifier to polymerize the acrylic monomer, thereby obtaining a latex in which an acrylic polymer is dispersed in water.

[0013] The acrylic monomer may include at least one monomer selected from the group consisting of an alkyl acrylate, an alkyl methacrylate, and an alkoxyalkyl acrylate.

[0014] The alkyl acrylate is represented by the following formula (1). [ka] In the formula, R 1 represents an alkyl group.

[0015] The alkyl group in the alkyl acrylate ester (R 1 The alkyl group (R ) in the alkyl acrylate ester may be linear or branched. 1 The number of carbon atoms in the alkyl acrylate may be 1 or more and 16 or less. Specific examples of the alkyl acrylate include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isoamyl acrylate, n-hexyl acrylate, 2-methylpentyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, hexadecyl acrylate, 1-adamantyl acrylate, cyclohexyl acrylate, and the like. These alkyl acrylates may be used alone or in combination of two or more.

[0016] The content of the acrylic acid alkyl ester may be 40% by mass or more, 50% by mass or more, or 60% by mass or more, and may be 99% by mass or less, 95% by mass or less, or 90% by mass or less, based on the total mass of the acrylic monomers.

[0017] The alkyl acrylate ester has an alkyl group having 3 or less carbon atoms (R 1 an alkyl acrylate having 3 or less carbon atoms (R 1 wherein the alkyl group has 4 or more carbon atoms) and an alkyl acrylate ester (second alkyl acrylate ester).

[0018] The number of carbon atoms in the alkyl group in the first alkyl acrylate may be 1 or more, may be 2 or less, or may be 2. The first alkyl acrylate is preferably ethyl acrylate. The number of carbon atoms in the alkyl group in the second alkyl acrylate may be 8 or less, 6 or less, or 5 or less, or may be 4. The second alkyl acrylate is preferably n-butyl acrylate.

[0019] The content of the first alkyl acrylate may be 10% by mass or more, 20% by mass or more, or 30% by mass or more, and may be 70% by mass or less, 60% by mass or less, or 50% by mass or less, based on the total mass of the acrylic monomers.

[0020] The content of the second alkyl acrylate may be 20% by mass or more, 30% by mass or more, or 40% by mass or more, and may be 70% by mass or less, 60% by mass or less, or 50% by mass or less, based on the total mass of the acrylic monomers.

[0021] The alkyl methacrylate is represented by the following formula (2). [ka] In the formula, R 2 represents an alkyl group.

[0022] The alkyl group in the alkyl methacrylate ester (R 2The alkyl group (R ) in the alkyl methacrylate ester may be linear or branched. 2 The number of carbon atoms in may be 1 or more, may be 4 or less, preferably 2 or more or 3 or more, and may be 3. Specific examples of the methacrylic acid alkyl ester include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, and the like. These methacrylic acid alkyl esters may be used alone or in combination of two or more. The methacrylic acid alkyl ester is preferably n-butyl methacrylate.

[0023] The content of the alkyl methacrylate ester (preferably an alkyl methacrylate ester having an alkyl group having 3 or more carbon atoms) based on the total mass of the acrylic monomer may be 3 mass% or more, 5 mass% or more, or 7 mass% or more, and is 40 mass% or less, 35 mass% or less, 30 mass% or less, 25 mass% or less, 20 mass% or less, 15 mass% or less, or 13 mass% or less.

[0024] The alkoxyalkyl acrylate is represented by the following formula (3). [ka] In the formula, R 3 represents an alkylene group, R 4 represents an alkyl group.

[0025] The alkylene group (R 3 ) and alkyl groups (R 4 The alkylene group (R ) in the alkoxyalkyl acrylate ester may be linear or branched. 3 The number of carbon atoms in the alkyl group (R ) may be 1 or more, or 2 or more, and may be 4 or less, or 3 or less. 4 ) may have 1 or more carbon atoms, and may have 4 or less, 3 or less, or 2 or less carbon atoms.

[0026] Specific examples of alkoxyalkyl acrylates include 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, 2-(n-propoxy)ethyl acrylate, 2-(n-butoxy)ethyl acrylate, 3-methoxypropyl acrylate, 3-ethoxypropyl acrylate, 2-(n-propoxy)propyl acrylate, and 2-(n-butoxy)propyl acrylate. These alkoxyalkyl acrylates may be used alone or in combination of two or more.

[0027] The content of the alkoxyalkyl acrylate may be 5% by mass or more, 10% by mass or more, or 12% by mass or more, and may be 30% by mass or less, 25% by mass or less, or 20% by mass or less, based on the total mass of the acrylic monomers.

[0028] The acrylic monomer may further include a crosslinking monomer. The crosslinking monomer is a monomer that is copolymerizable with an acrylic acid alkyl ester (further, a methacrylic acid alkyl ester and an acrylic acid alkoxyalkyl ester) and has a crosslinkable group that forms a crosslinking site (also called a crosslinking point). The crosslinking monomer has a polymerizable carbon-carbon double bond, and has, for example, an acryloyl group, a methacryloyl group, an allyl group, a methallyl group, a vinyl group, or an alkenylene group. Examples of the crosslinking group include a carboxyl group, an epoxy group, and an active chlorine group. The crosslinking monomer may have one or more of these functional groups.

[0029] Examples of crosslinkable monomers having a carboxyl group as a crosslinkable group include acrylic acid, methacrylic acid, crotonic acid, 2-pentenoic acid, maleic acid, fumaric acid, itaconic acid, and maleic acid monoalkyl esters.

[0030] Examples of cross-linking monomers having an epoxy group as a cross-linkable group include glycidyl acrylate, glycidyl methacrylate, allyl glycidyl ether, and methallyl glycidyl ether.

[0031] Examples of crosslinkable monomers having an active chlorine group as a crosslinkable group include 2-chloroethyl vinyl ether, 2-chloroethyl acrylate, vinylbenzyl chloride, vinyl chloroacetate, and allyl chloroacetate.

[0032] The content of the crosslinking monomer may be 0.5% by mass or more, 1% by mass or more, or 1.2% by mass or more, and may be 8% by mass or less, 5% by mass or less, or 3% by mass or less, based on the total mass of the acrylic monomers.

[0033] The acrylic monomer may further include other monomers copolymerizable with the above-mentioned monomers, such as ethylene, methacrylic acid alkoxy esters, alkyl vinyl ketones, vinyl ethers, allyl ethers, vinyl aromatic compounds, vinyl nitriles, maleic acid dialkyl esters, fumaric acid dialkyl esters, itaconic acid dialkyl esters, citraconic acid dialkyl esters, mesaconic acid dialkyl esters, 2-pentenedioic acid dialkyl esters, and acetylenedicarboxylic acid dialkyl esters.

[0034] The nonionic emulsifier may include at least one selected from the group consisting of ether-type nonionic emulsifiers, ester-type nonionic emulsifiers, ether-ester-type nonionic emulsifiers, nitrogen-containing nonionic emulsifiers, and polyvinyl alcohol-based emulsifiers.

[0035] Examples of ether-type nonionic emulsifiers include polyoxyethylene alkyl ethers, polyoxyethylene alkyl allyl ethers, polyoxyalkylene alkyl ethers, polyoxyethylene alkenyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene polyoxypropylene copolymers, polyoxyethylene lauryl glycol, and polyoxypropylene glycol.

[0036] Examples of the ester-type nonionic emulsifier include sorbitan fatty acid esters and glycerin fatty acid esters. The sorbitan fatty acid esters may be, for example, monoesters. The glycerin fatty acid esters may be, for example, monoesters or diesters.

[0037] Examples of the ether ester type nonionic emulsifier include polyoxyethylene fatty acid esters and polyoxyethylene sorbitan fatty acid esters. The polyoxyethylene fatty acid esters may be, for example, monoesters or diesters. The polyoxyethylene sorbitan fatty acid esters may be, for example, monoesters.

[0038] Examples of nitrogen-containing nonionic emulsifiers include polyoxyethylene alkylamines, polyoxyethylene fatty acid monoethanolamides, and fatty acid diethanolamides.

[0039] The polyvinyl alcohol emulsifier may be a fully saponified polyvinyl alcohol or a partially saponified polyvinyl alcohol, preferably a partially saponified polyvinyl alcohol. The saponification degree of the polyvinyl alcohol may be 60 mol% or more, 70 mol% or more, or 80 mol% or more, and may be 100 mol% or less, 99 mol% or less, or 90 mol% or less. The saponification degree of the polyvinyl alcohol means a value measured according to JIS K6726 "3.5 Saponification degree".

[0040] The amount of the nonionic emulsifier added may be 1 part by mass or more, 1.5 parts by mass or more, 2 parts by mass or more, 2.5 parts by mass or more, 3 parts by mass or more, 3.5 parts by mass or more, 4 parts by mass or more, or 4.5 parts by mass or more, relative to 100 parts by mass of the total mass of the acrylic monomer. The amount of the nonionic emulsifier added may be preferably 10 parts by mass or less, 9 parts by mass or less, 8 parts by mass or less, 7 parts by mass or less, 6 parts by mass or less, or 5 parts by mass or less, relative to 100 parts by mass of the total mass of the acrylic monomer, from the viewpoint of further improving the water resistance of the crosslinked product, lowering the toluene insoluble content of the acrylic rubber, and improving the flex fatigue resistance of the crosslinked product.

[0041] The polymerization initiator may be, for example, an azo compound such as azobisisobutyronitrile, an organic peroxide such as tert-butyl hydroperoxide, cumene hydroperoxide, or benzoyl peroxide, or an inorganic peroxide such as sodium persulfate or ammonium persulfate, and is preferably tert-butyl hydroperoxide.

[0042] When polymerizing the acrylic monomer, a pH adjuster may be further used. The pH adjuster may be, for example, an alkali metal salt such as sodium acetate, sodium hydroxide, potassium hydroxide, sodium phosphate, or sodium citrate, and is preferably sodium acetate. The amount of the pH adjuster added may be, for example, 0.1 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the total amount of the monomer.

[0043] The acrylic polymer in the latex obtained in step S1 may contain the above-mentioned acrylic monomer as a monomer unit. That is, the acrylic polymer may contain at least one monomer unit selected from the group consisting of an alkyl acrylate, an alkyl methacrylate, and an alkoxyalkyl acrylate.

[0044] In this latex, more than 0% by mass and 70% by mass or less of the total mass of the nonionic emulsifier is fixed to the acrylic polymer. In this specification, the amount of the nonionic emulsifier fixed to the acrylic polymer is obtained by subtracting the amount of the nonionic emulsifier not fixed to the acrylic polymer from the total amount (charged amount) of the nonionic emulsifier in the latex. The amount of the nonionic emulsifier not fixed to the acrylic polymer is defined as the amount of the nonionic emulsifier contained in the supernatant liquid after centrifuging the latex at 10,000 rpm x 30 minutes in a centrifuge and separating the precipitated solids. The amount of the nonionic emulsifier contained in the supernatant liquid is measured by a method appropriately selected depending on the type of nonionic emulsifier. For example, when the nonionic emulsifier is polyvinyl alcohol, the amount of polyvinyl alcohol contained in the supernatant liquid is measured by the method described in the examples.

[0045] That is, in this specification, the nonionic emulsifier fixed to the acrylic polymer is defined as the nonionic emulsifier contained in the precipitated solids when the latex is centrifuged at 10000 rpm for 30 minutes (the nonionic emulsifier is not detached from the acrylic polymer). Also, in this specification, the nonionic emulsifier not fixed to the acrylic polymer is defined as the nonionic emulsifier contained in the supernatant when the latex is centrifuged at 10000 rpm for 30 minutes (the nonionic emulsifier is detached from the acrylic polymer).

[0046] The lower limit of the amount of the nonionic emulsifier fixed to the acrylic polymer may be, based on the total mass of the nonionic emulsifier, preferably 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, 1.5% by mass or more, 2% by mass or more, 3% by mass or more, 4% by mass or more, 5% by mass or more, 6% by mass or more, 7% by mass or more, 8% by mass or more, 9% by mass or more, 10% by mass or more, 12% by mass or more, 14% by mass or more, 16% by mass or more, 18% by mass or more, 20% by mass or more, 25% by mass or more, 30% by mass or more, 40% by mass or more, or 45% by mass or more, from the viewpoint of further improving the tensile strength at break of the crosslinked product and improving the copper damage resistance of the crosslinked product. The upper limit of the amount of nonionic emulsifier fixed to the acrylic polymer may be, based on the total mass of the nonionic emulsifier, from the viewpoints of further improving the water resistance of the crosslinked product, reducing the toluene-insoluble content of the acrylic rubber, and improving the flex fatigue resistance of the crosslinked product, preferably 68% by mass or less, 65% by mass or less, 60% by mass or less, 55% by mass or less, 50% by mass or less, 40% by mass or less, 30% by mass or less, 25% by mass or less, 20% by mass or less, 15% by mass or less, or 10% by mass or less.

[0047] The amount of nonionic emulsifier that is not fixed to the acrylic polymer may be, based on the total mass of the nonionic emulsifier, from the viewpoints of further improving the water resistance of the crosslinked product, reducing the toluene-insoluble content of the acrylic rubber, and improving the flex fatigue resistance of the crosslinked product, preferably 30 mass% or more, 32 mass% or more, 35 mass% or more, 40 mass% or more, 45 mass% or more, 50 mass% or more, 60 mass% or more, 70 mass% or more, 75 mass% or more, 80 mass% or more, 85 mass% or more, or 90 mass% or more. The amount of nonionic emulsifier that is not fixed to the acrylic polymer, based on the total mass of the nonionic emulsifier, from the viewpoint of further improving the tensile strength at break of the crosslinked product and improving the copper damage resistance of the crosslinked product, may be preferably less than 100% by mass, 99.9% by mass or less, 99.5% by mass or less, 99% by mass or less, 98.5% by mass or less, 98% by mass or less, 97% by mass or less, 96% by mass or less, 95% by mass or less, 94% by mass or less, 93% by mass or less, 92% by mass or less, 91% by mass or less, 90% by mass or less, 88% by mass or less, 86% by mass or less, 84% by mass or less, 82% by mass or less, 80% by mass or less, 75% by mass or less, 70% by mass or less, 60% by mass or less, or 55% by mass or less.

[0048] The total mass of the nonionic emulsifier in the latex may be 1 part by mass or more, 1.5 parts by mass or more, 2 parts by mass or more, 2.5 parts by mass or more, 3 parts by mass or more, 3.5 parts by mass or more, 4 parts by mass or more, or 4.5 parts by mass or more, relative to 100 parts by mass of the total mass of the acrylic polymer. The total mass of the nonionic emulsifier in the latex may be preferably 10 parts by mass or less, 9 parts by mass or less, 8 parts by mass or less, 7 parts by mass or less, 6 parts by mass or less, or 5 parts by mass or less, relative to 100 parts by mass of the total mass of the acrylic polymer, from the viewpoint of further improving the water resistance of the crosslinked product, lowering the toluene insoluble content of the acrylic rubber, and improving the flex fatigue resistance of the crosslinked product.

[0049] In order to fix a specific amount of the nonionic emulsifier in the latex to the acrylic polymer, it is important to add a monomer mixture containing an acrylic monomer and a polymerization initiator separately to the suspension of the nonionic emulsifier in step S1, and to adjust the amount of the polymerization initiator to be added within a specific range. Also, in step S1, the amount of the nonionic emulsifier fixed to the acrylic polymer can be adjusted by increasing or decreasing the amount of the acrylic monomer added at the beginning of the polymerization of the acrylic monomer, or by adjusting the polymerization temperature and polymerization time.

[0050] Subsequently, in step S2, a coagulant is added to the latex obtained in step S1 to coagulate the acrylic polymer. Examples of the coagulant include ammonium salts, monovalent to trivalent metal salts, inorganic acids, and organic acids. Examples of the ammonium salts include ammonium borate, ammonium sulfate, and ammonium chloride. Examples of the monovalent to trivalent metal salts include sodium salts, magnesium salts, calcium salts, aluminum salts, and zinc salts. Examples of the sodium salts include sodium borate, sodium sulfate, and sodium chloride. Examples of the magnesium salts include magnesium sulfate, magnesium chloride, and magnesium nitrate. Examples of the calcium salts include calcium sulfate, calcium chloride, and calcium nitrate. Examples of the aluminum salts include aluminum sulfate and aluminum chloride. Examples of the zinc salts include zinc chloride and zinc acetate. Examples of the inorganic acids include hydrochloric acid, sulfuric acid, and nitric acid. Examples of the organic acids include formic acid and acetic acid.

[0051] The amount of the coagulant added may be 0.5 parts by mass or more, 1 part by mass or more, or 2 parts by mass or more, and may be 150 parts by mass or less, 50 parts by mass or less, or 20 parts by mass or less, relative to 100 parts by mass of the total mass of the acrylic polymer.

[0052] In step S2, the solidified acrylic polymer is then washed with water and dried. When washing with water, a part of the nonionic emulsifier that is not fixed to the acrylic polymer in the latex (the nonionic emulsifier that is detached by washing with water even without the above-mentioned centrifugation) is removed. Therefore, by going through step S2, the amount of the nonionic emulsifier that is not fixed to the acrylic rubber in the obtained acrylic rubber (rubber composition) can be less than the amount of the nonionic emulsifier that is not fixed to the acrylic polymer in the latex.

[0053] By the above-mentioned manufacturing method, an acrylic rubber coexisting with a nonionic emulsifier (a rubber composition containing an acrylic rubber and a nonionic emulsifier) ​​can be obtained. That is, another embodiment of the present invention is a rubber composition containing an acrylic rubber and a nonionic emulsifier.

[0054] The acrylic rubber contains the above-mentioned acrylic monomer as a monomer unit. That is, the acrylic polymer may contain at least one monomer unit selected from the group consisting of an alkyl acrylate, an alkyl methacrylate, and an alkoxyalkyl acrylate. The acrylic rubber may further contain a crosslinking monomer as a monomer unit, or may further contain other monomers.

[0055] The nonionic emulsifier contained in the rubber composition may be derived from the nonionic emulsifier used in the above-mentioned step S1. Details of the nonionic emulsifier are as described above. In the rubber composition, more than 0 mass % and 80 mass % or less of the total mass of the nonionic emulsifier is fixed to the acrylic rubber.

[0056] In this specification, the amount of nonionic emulsifier fixed to the acrylic rubber is obtained by subtracting the amount of nonionic emulsifier not fixed to the acrylic rubber (and the amount of nonionic emulsifier removed by washing when the acrylic rubber is washed) from the total amount (charged amount) of nonionic emulsifier. The amount of nonionic emulsifier not fixed to the acrylic rubber is defined as the amount of nonionic emulsifier contained in the supernatant after centrifuging a solution in which the acrylic rubber is dissolved (see Examples for details) at 10,000 rpm for 30 minutes in a centrifuge. The amount of nonionic emulsifier contained in the supernatant is measured by a method appropriately selected according to the type of nonionic emulsifier. For example, when the nonionic emulsifier is polyvinyl alcohol, the amount of polyvinyl alcohol contained in the supernatant is measured by the method described in the Examples.

[0057] That is, in this specification, a nonionic emulsifier fixed to an acrylic rubber is defined as a nonionic emulsifier contained in the precipitated solids when an acrylic rubber solution is centrifuged at 10,000 rpm for 30 minutes (a nonionic emulsifier that does not detach from the acrylic rubber). Also, in this specification, a nonionic emulsifier not fixed to an acrylic rubber is defined as a nonionic emulsifier contained in the supernatant when an acrylic rubber solution is centrifuged at 10,000 rpm for 30 minutes (a nonionic emulsifier that has detached from the acrylic rubber).

[0058] The lower limit of the amount of nonionic emulsifier fixed to the acrylic rubber may be, based on the total mass of the nonionic emulsifier, preferably 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, 1.5% by mass or more, 2% by mass or more, 3% by mass or more, 4% by mass or more, 5% by mass or more, 6% by mass or more, 7% by mass or more, 8% by mass or more, 9% by mass or more, 10% by mass or more, 12% by mass or more, 14% by mass or more, 16% by mass or more, 18% by mass or more, 20% by mass or more, 25% by mass or more, 30% by mass or more, 40% by mass or more, 45% by mass or more, or 50% by mass or more, from the viewpoint of further improving the tensile strength at break of the crosslinked product and improving the copper damage resistance of the crosslinked product. The upper limit of the amount of nonionic emulsifier fixed to the acrylic rubber may be, based on the total mass of the nonionic emulsifier, from the viewpoints of further improving the water resistance of the crosslinked product, reducing the toluene-insoluble content of the acrylic rubber, and improving the flex fatigue resistance of the crosslinked product, preferably 75% by mass or less, 70% by mass or less, 68% by mass or less, 65% by mass or less, 60% by mass or less, 55% by mass or less, 50% by mass or less, 40% by mass or less, 30% by mass or less, 25% by mass or less, 20% by mass or less, or 15% by mass or less.

[0059] The amount of nonionic emulsifier that is not fixed to the acrylic rubber may be, based on the total mass of the nonionic emulsifier, from the viewpoints of further improving the water resistance of the crosslinked product, reducing the toluene-insoluble content of the acrylic rubber, and improving the flex fatigue resistance of the crosslinked product, preferably 20 mass% or more, 25 mass% or more, 30 mass% or more, 32 mass% or more, 35 mass% or more, 40 mass% or more, 45 mass% or more, 50 mass% or more, 60 mass% or more, 70 mass% or more, 75 mass% or more, 80 mass% or more, or 85 mass% or more. The amount of nonionic emulsifier that is not fixed to the acrylic rubber, based on the total mass of the nonionic emulsifier, from the viewpoint of further improving the tensile strength at break of the crosslinked product and improving the copper damage resistance of the crosslinked product, may be preferably less than 100% by mass, 99.9% by mass or less, 99.5% by mass or less, 99% by mass or less, 98.5% by mass or less, 98% by mass or less, 97% by mass or less, 96% by mass or less, 95% by mass or less, 94% by mass or less, 93% by mass or less, 92% by mass or less, 91% by mass or less, 90% by mass or less, 88% by mass or less, 86% by mass or less, 84% by mass or less, 82% by mass or less, 80% by mass or less, 75% by mass or less, 70% by mass or less, 60% by mass or less, 55% by mass or less, or 50% by mass or less.

[0060] The total mass of the nonionic emulsifier in the rubber composition may be 0.5 parts by mass or more, 1 part by mass or more, 1.5 parts by mass or more, 2 parts by mass or more, 2.5 parts by mass or more, 3 parts by mass or more, 3.5 parts by mass or more, or 4 parts by mass or more, relative to 100 parts by mass of the total mass of the acrylic rubber. The total mass of the nonionic emulsifier in the rubber composition may be preferably 10 parts by mass or less, 9 parts by mass or less, 8 parts by mass or less, 7 parts by mass or less, 6 parts by mass or less, 5 parts by mass or less, 4.5 parts by mass or less, or 4 parts by mass or less, relative to 100 parts by mass of the total mass of the acrylic rubber, from the viewpoint of further improving the water resistance of the crosslinked product, lowering the toluene insoluble content of the acrylic rubber, and improving the flex fatigue resistance of the crosslinked product.

[0061] The rubber composition may further contain a crosslinking agent. The rubber composition may further contain a crosslinking accelerator. In this case, the rubber composition is kneaded at a temperature equal to or lower than the crosslinking temperature, and then heated at a predetermined crosslinking temperature to obtain a crosslinked product. Another embodiment of the present invention is a crosslinked product of the above rubber composition.

[0062] The heating conditions for crosslinking can be appropriately set depending on the compounding of the rubber composition and the type of crosslinking agent. The heating temperature may be 100° C. or higher and 200° C. or lower. The heating time may be 1 hour or higher and 10 hours or lower. As the heating method, a method used for crosslinking rubber, such as heat press heating, steam heating, or oven heating, can be used.

[0063] The apparatus for kneading, molding, and crosslinking the rubber composition and the apparatus for kneading and molding the crosslinked product of the rubber composition may be any apparatus generally used for rubber compositions. Examples of the kneading apparatus that may be used include a roll, a kneader, a Banbury mixer, an internal mixer, and a twin-screw extruder.

[0064] The crosslinking agent is not particularly limited as long as it is one that is usually used for crosslinking acrylic rubber. For example, when the acrylic rubber contains a crosslinking monomer having a carboxyl group as a monomer unit, the crosslinking agent is preferably a polyamine compound and a carbonate of the polyamine compound, more preferably a polyamine compound having 4 to 30 carbon atoms and a carbonate thereof.

[0065] Specific examples of polyamine compounds include 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-diaminodiphenyl sulfide, 1,3-bis(4-aminophenoxy)-2,2-dimethylpropane, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)pentane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]sulfone, 4,4'-diaminodiphenylsulfone, and bis(4-aminophenoxy)phenyl. (i) Aromatic polyamine compounds such as phenylsulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 4,4'-diaminobenzanilide, and bis[4-(4-aminophenoxy)phenyl]sulfone; and aliphatic polyamine compounds such as hexamethylenediamine, hexamethylenediamine carbamate, N,N'-dicinnamylidene-1,6-hexanediamine, diethylenetriamine, triethylenetetramine, and tetraethylenepentamine.

[0066] The content of the crosslinking agent in the rubber composition may be 0.1 parts by mass or more, 0.2 parts by mass or more, or 0.3 parts by mass or more, and may be 5 parts by mass or less, 4 parts by mass or less, or 3 parts by mass or less, relative to 100 parts by mass of the acrylic rubber.

[0067] The crosslinking accelerator is not particularly limited, but when the crosslinking agent is a polyamine compound or a carbonate thereof, examples of the crosslinking accelerator include aliphatic monovalent secondary amine compounds, aliphatic monovalent tertiary amine compounds, guanidine compounds, imidazole compounds, quaternary onium salts, tertiary phosphine compounds, alkali metal salts of weak acids, and diazabicycloalkene compounds. The crosslinking accelerator can be used alone or in combination of two or more.

[0068] Examples of the aliphatic monovalent secondary amine compound include dimethylamine, diethylamine, di-n-propylamine, diallylamine, diisopropylamine, di-n-butylamine, di-t-butylamine, di-sec-butylamine, dihexylamine, diheptylamine, dioctylamine, dinonylamine, didecylamine, diundecylamine, didodecylamine, ditridecylamine, ditetradecylamine, dipentadecylamine, dicetylamine, di-2-ethylhexylamine, dioctadecylamine, di-cis-9-octadecenylamine, and dinonadecylamine.

[0069] Examples of the aliphatic monovalent tertiary amine compounds include trimethylamine, triethylamine, tri-n-propylamine, triallylamine, triisopropylamine, tri-n-butylamine, tri-t-butylamine, tri-sec-butylamine, tripentylamine, trihexylamine, triheptylamine, trioctylamine, trinonylamine, tridecylamine, triundecylamine, tridodecylamine, tridecylamine, tritetradecylamine, tripentadecylamine, tricetylamine, tri-2-ethylhexylamine, trioct ... Examples of the amines include octadecylamine, tri-cis-9-octadecenylamine, trinonadecylamine, N,N-dimethyldecylamine, N,N-dimethyldodecylamine, N,N-dimethyltetradecylamine, N,N-dimethylcetylamine, N,N-dimethyloctadecylamine, N,N-dimethylbehenylamine, N-methyldidecylamine, N-methyldidodecylamine, N-methylditetradecylamine, N-methyldicetylamine, N-methyldioctadecylamine, N-methyldibehenylamine, and dimethylcyclohexylamine.

[0070] The guanidine compounds include 1,3-di-o-tolylguanidine, 1,3-diphenylguanidine, and the like.

[0071] The imidazole compounds include 2-methylimidazole, 2-phenylimidazole, and the like.

[0072] The quaternary onium salt is not particularly limited, but examples thereof include tetra-n-butylammonium chloride, trimethylphenylammonium chloride, trimethylstearylammonium chloride, trimethyllaurylammonium chloride, trimethylcetylammonium chloride, dimethyldistearylammonium chloride, tributylbenzylammonium chloride, tetra-n-butylammonium bromide, methyltriphenylammonium bromide, ethyltriphenylammonium bromide, trimethylphenylammonium bromide, trimethylbenzylammonium bromide, trimethylstearylammonium bromide, and tetrabutylammonium thiocyanate. and phosphonium salts such as tetra-n-butylphosphonium chloride, tetra-n-butylphosphonium bromide, methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, hexyltriphenylphosphonium bromide, benzyltriphenylphosphonium bromide, tetraphenylphosphonium chloride, tetraphenylphosphonium bromide, 4-butoxybenzyltriphenylphosphonium bromide, allyltributylphosphonium chloride, 2-propynyltriphenylphosphonium bromide, and methoxypropyltributylphosphonium chloride.

[0073] Tertiary phosphine compounds include triphenylphosphine, tri-p-tolylphosphine, and the like.

[0074] Examples of the alkali metal salts of weak acids include inorganic weak acid salts such as sodium and potassium phosphates and carbonates, and organic weak acid salts such as sodium and potassium stearates and laurates.

[0075] Examples of the diazabicycloalkene compound include 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), 1,5-diazabicyclo[4.3.0]nonene-5 (DBN), and 1,4-diazabicyclo[2.2.2]octane (DABCO). These diazabicycloalkene compounds may form salts with, for example, hydrochloric acid, sulfuric acid, carboxylic acid, sulfonic acid, and phenol. Examples of the carboxylic acid include octyl acid, oleic acid, formic acid, orthophthalic acid, and adipic acid. Examples of the sulfonic acid include benzenesulfonic acid, toluenesulfonic acid, dodecylbenzenesulfonic acid, and naphthalenesulfonic acid.

[0076] The content of the crosslinking accelerator may be 0.1 parts by mass or more, 0.2 parts by mass or more, or 0.3 parts by mass or more, and 5 parts by mass or less, 4 parts by mass or less, or 3 parts by mass or less, based on 100 parts by mass of the acrylic rubber.

[0077] The rubber composition may further contain other additives, such as a filler (reinforcing agent), a plasticizer, a lubricant, an antioxidant, a stabilizer, and a silane coupling agent.

[0078] The total content of the other additives in the rubber composition may be 0.1 part by mass or more or 0.2 part by mass or more, and 90 parts by mass or less or 80 parts by mass or less, relative to 100 parts by mass of the acrylic rubber.

[0079] The above-mentioned rubber composition is preferably used as a rubber composition for a seal (also called a sealing member) or a hose (also called a hose member). The rubber composition can also be used as a rubber composition for an anti-vibration rubber (also called an anti-vibration rubber member). The cross-linked product of the above-mentioned rubber composition is preferably used as a seal or a hose. That is, another embodiment of the present invention is a seal or a hose containing the above-mentioned cross-linked product. The cross-linked product can also be used as an anti-vibration rubber. That is, another embodiment of the present invention is an anti-vibration rubber containing the above-mentioned cross-linked product. Examples of the hose (hose member) include a rubber hose. Examples of the seal (seal member) include a gasket and a packing. These members may be made of only the cross-linked product of the rubber composition, or may include the cross-linked product and other parts.

[0080] Specific examples of hoses (hose members) include transmission oil cooler hoses, engine oil cooler hoses, air duct hoses, turbo intercooler hoses, hot air hoses, radiator hoses, power steering hoses, fuel system hoses, drain system hoses, etc. for automobiles, construction machines, hydraulic equipment, etc. The hose member may have a reinforcing yarn or wire in an intermediate layer or the outermost layer of the hose.

[0081] Specific examples of seals (sealing members) include engine head cover gaskets, oil pan gaskets, oil seals, lip seal packings, O-rings, transmission seal gaskets, crankshafts, camshaft seal gaskets, valve stems, power steering seals, belt cover seals, constant velocity joint boot materials, and rack and pinion boot materials.

[0082] Specific examples of anti-vibration rubber (anti-vibration rubber member) include, for example, damper pulleys, center support cushions, and suspension bushes. EXAMPLES

[0083] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0084] Example 1 A pressure-resistant reaction vessel with an internal volume of 40 liters was charged with 16.8 kg of a 4% by mass aqueous solution of a nonionic emulsifier (polyvinyl alcohol) and 22 g of sodium acetate, which were mixed thoroughly in advance with a stirrer to prepare a uniform suspension. After replacing the air in the upper part of the vessel with nitrogen, stirring was continued, and the vessel was kept at 45°C, and then 11.2 kg of a monomer mixture consisting of (meth)acrylic monomers containing ethyl acrylate and n-butyl acrylate and monobutyl maleate and 2 liters of an aqueous t-butyl hydroperoxide solution (0.25% by mass) were separately added by pressure to start polymerization. The temperature in the vessel was kept at 45°C, and the reaction was terminated after 6.5 hours. As a result, a latex containing an acrylic polymer dispersed in water and a nonionic emulsifier was obtained. 20 liters of an aqueous sodium borate solution (3.5% by mass) was added as a coagulant to the obtained latex to coagulate the acrylic polymer. Next, the solidified acrylic polymer was washed with water, and then dehydrated and dried to obtain an acrylic rubber (a rubber composition containing an acrylic rubber and a nonionic emulsifier).

[0085] The acrylic polymer and acrylic rubber had a monomer composition (hereinafter referred to as "monomer composition A") of 50.0% by mass of ethyl acrylate, 48.5% by mass of n-butyl acrylate, and 1.5% by mass of monobutyl maleate. In addition, the total mass (parts by mass) of the nonionic emulsifier in the latex relative to 100 parts by mass of the total mass of the acrylic polymer in the latex, the ratio of the nonionic emulsifier fixed to the acrylic polymer in the latex (% by mass based on the total mass of the nonionic emulsifier in the latex), the total mass (parts by mass) of the nonionic emulsifier in the rubber composition relative to 100 parts by mass of the total mass of the acrylic rubber in the rubber composition, and the ratio of the nonionic emulsifier fixed to the acrylic rubber in the rubber composition (% by mass based on the total mass of the nonionic emulsifier in the rubber composition) are shown in Tables 1 and 2.

[0086] The proportion of the nonionic emulsifier fixed to the acrylic polymer in the latex was measured by the following procedure. First, M E (g) Latex M containing a nonionic emulsifier L 50 g of sample (kg) diluted 20 times with pure water was placed in a centrifuge tube and centrifuged at 10,000 rpm for 30 minutes using a centrifuge (Hitachi "CT15D"). The supernatant after centrifugation was placed in a 100 mL plastic bottle, and the mass M S (g) was weighed. 1 mL of this supernatant, 15 mL of 4 mass% boric acid aqueous solution, and 3 mL of 0.05 mol iodine solution were added, and pure water was added to make up to 50 mL to obtain a measurement sample (a sample in which the latex was diluted 1000 times). The absorbance Abs of this measurement sample at a wavelength of 650 nm was measured using a spectrophotometer. Next, the concentration C of the nonionic emulsifier that is not fixed to the acrylic polymer in the latex free (g / kg) using the following formula: C free (g / kg) = α(mg / L) × Abs × M S (g) / 50(g) It was calculated by:

[0087] In the above formula, the density of the supernatant is converted to 1 g / mL, and the measurement sample is latex diluted 1000 times, so C free The unit of is g / kg. The concentration coefficient α (mg / L) was calculated by preparing the measurement sample and measuring the absorbance at a wavelength of 650 nm in the same manner as for the supernatant liquid for each aqueous solution of the nonionic emulsifier (same polyvinyl alcohol as above) with concentrations of 2, 10, 20, 30, and 40 mg / L, and approximating the relationship of concentration of each aqueous solution = α × absorbance.

[0088] And the above C free (g / kg) to determine the mass M of the nonionic emulsifier that is not fixed to the acrylic polymer in the latex. free (g)=C free (g / kg) x M L(kg) was calculated. Finally, the ratio of the nonionic emulsifier fixed to the acrylic polymer in the latex (mass%) = [M E (g)-M free (g)] / M E (g) x 100 was calculated.

[0089] The proportion of the nonionic emulsifier fixed to the acrylic rubber in the rubber composition was measured by the following procedure. First, 0.3 g of the rubber composition was prepared and precisely weighed into a 100 mL Erlenmeyer flask. About 20 mL of chloroform (CHCl3) was added to this rubber composition, and the mixture was shaken to dissolve the rubber composition. Then, 10 mL of dimethyl sulfoxide (DMSO) was added and heated in a water bath at 90°C or higher for 1 hour. Next, 20 mL of hot water at 80°C or higher was added little by little, and the mixture was heated in a water bath for about 30 minutes to remove the chloroform, and then allowed to cool. The sample after cooling was centrifuged at 10,000 rpm x 30 minutes using a centrifuge (Hitachi "CT15D"). The supernatant after centrifugation was made up to 100 mL and filtered through a 200 mesh wire mesh to obtain a sample containing a nonionic emulsifier that was not fixed to the acrylic rubber. The concentration C of the nonionic emulsifier that was not fixed to the acrylic polymer in the latex was measured for this sample. free The proportion of the nonionic emulsifier not fixed to the acrylic rubber in the rubber composition was determined in the same manner as in (g / kg). The amount of the nonionic emulsifier fixed to the acrylic rubber was determined by subtracting the amount of the nonionic emulsifier not fixed to the acrylic rubber thus determined and the amount of the nonionic emulsifier removed by washing with water from the amount of the nonionic emulsifier charged.

[0090] Example 2 An acrylic rubber (rubber composition) was obtained in the same manner as in Example 1, except that the amount of the t-butyl hydroperoxide aqueous solution (0.25% by mass) added was changed to 0.75 times.

[0091] Example 3 An acrylic rubber (rubber composition) was obtained in the same manner as in Example 1, except that the amount of t-butyl hydroperoxide aqueous solution (0.25% by mass) added was changed to 0.75 times and the amount of monomer mixture added at the initial stage of polymerization was reduced by about 20%.

[0092] Example 4 An acrylic rubber (rubber composition) was obtained in the same manner as in Example 1, except that the amount of t-butyl hydroperoxide aqueous solution (0.25% by mass) added was changed to 0.75 times, the amount of monomer mixture added at the beginning of polymerization was reduced by about 40%, and the polymerization temperature was changed to 35°C.

[0093] Example 5 An acrylic rubber (rubber composition) was obtained in the same manner as in Example 1, except that the amount of t-butyl hydroperoxide aqueous solution (0.25% by mass) added was changed to 0.5 times, the amount of monomer mixture added at the initial stage of polymerization was reduced by about 75%, the polymerization temperature was changed to 35°C, and the reaction time was changed to 12 hours.

[0094] Comparative Example 1 An acrylic rubber (rubber composition) was obtained in the same manner as in Example 1, except that the amount of the t-butyl hydroperoxide aqueous solution (0.25% by mass) added was doubled and the polymerization temperature was changed to 55°C.

[0095] Comparative Example 2 An acrylic rubber (rubber composition) was obtained in the same manner as in Example 1, except that the nonionic emulsifier was changed to an anionic emulsifier.

[0096] Example 6 An acrylic rubber (rubber composition) was obtained in the same manner as in Example 2, except that the concentration of the aqueous solution of the nonionic emulsifier was changed from 4% by mass to 8% by mass.

[0097] Example 7 An acrylic rubber (rubber composition) was obtained in the same manner as in Example 1, except that the monomer composition A of the acrylic polymer and acrylic rubber was changed to monomer composition B (68.5 mass% ethyl acrylate, 30.0 mass% n-butyl acrylate, and 1.5 mass% monobutyl maleate) by adjusting the compounding ratio of ethyl acrylate, n-butyl acrylate, and monobutyl maleate in the monomer mixture, and the amount of the t-butyl hydroperoxide aqueous solution (0.15 mass%) added was changed to 1.8 L.

[0098] Example 8 The monomer mixture was changed to a monomer mixture consisting of ethyl acrylate, n-butyl acrylate, n-butyl methacrylate, 2-methoxyethyl acrylate, and monobutyl maleate, and the monomer composition A of the acrylic polymer and acrylic rubber was changed to monomer composition C (ethyl acrylate 35.0 mass%, n-butyl acrylate 39.5 mass%, n-butyl methacrylate 9.5 mass%, 2-methoxyethyl acrylate 14.5 mass%, and monobutyl maleate 1.5 mass%). In addition, the amount of t-butyl hydroperoxide aqueous solution (0.25 mass%) added was changed to 1.5 L, and the polymerization temperature was changed to 45°C. Except for this, an acrylic rubber (rubber composition) was obtained in the same manner as in Example 1.

[0099] Example 9 An acrylic rubber (rubber composition) was obtained in the same manner as in Example 8, except that the amount of the t-butyl hydroperoxide aqueous solution (0.25% by mass) added was changed to 0.7 times.

[0100] Example 10 An acrylic rubber (rubber composition) was obtained in the same manner as in Example 1, except that the monomer mixture was changed to a monomer mixture consisting of ethyl acrylate, n-butyl acrylate, n-butyl methacrylate, and monobutyl maleate, and the monomer composition A of the acrylic polymer and acrylic rubber was changed to monomer composition D (25.0 mass% ethyl acrylate, 43.5 mass% n-butyl acrylate, 30.0 mass% n-butyl methacrylate, and 1.5 mass% monobutyl maleate).

[0101] Example 11 An acrylic rubber (rubber composition) was obtained in the same manner as in Example 1, except that the monomer mixture was changed to a monomer mixture consisting of ethyl acrylate, n-butyl acrylate, n-butyl methacrylate, and monobutyl maleate, and the monomer composition A of the acrylic polymer and acrylic rubber was changed to monomer composition E (ethyl acrylate 35.0 mass%, n-butyl acrylate 48.5 mass%, n-butyl methacrylate 15.0 mass%, and monobutyl maleate 1.5 mass%).

[0102] Example 12 An acrylic rubber (rubber composition) was obtained in the same manner as in Example 1, except that the monomer mixture was changed to a monomer mixture consisting of ethyl acrylate, n-butyl acrylate, 2-methoxyethyl acrylate, and monobutyl maleate, and the monomer composition A of the acrylic polymer and acrylic rubber was changed to monomer composition F (70.0 mass% ethyl acrylate, 13.5 mass% n-butyl acrylate, 15.0 mass% 2-methoxyethyl acrylate, and 1.5 mass% monobutyl maleate).

[0103] (Example 13) An acrylic rubber (rubber composition) was obtained in the same manner as in Example 1, except that the monomer mixture was changed to a monomer mixture consisting of ethyl acrylate, n-butyl acrylate, 2-methoxyethyl acrylate, and monobutyl maleate, and the monomer composition A of the acrylic polymer and acrylic rubber was changed to monomer composition G (ethyl acrylate 5.0 mass%, n-butyl acrylate 68.5 mass%, 2-methoxyethyl acrylate 25.0 mass%, and monobutyl maleate 1.5 mass%).

[0104] The Mooney viscosity ML(1+4)100° C. of the acrylic rubber (rubber composition) obtained in each of the Examples and Comparative Examples was measured according to the method specified in JIS K6300. The results are shown in Tables 1 and 2.

[0105] Moreover, each of the components shown below was blended with 100 parts by mass of the acrylic rubber (rubber composition) obtained in each of the Examples and Comparative Examples, and kneaded with an 8-inch open roll. Filler: Carbon black (Tokai Carbon Co., Ltd., SEAT SO) 55 parts by weight Lubricant A: 1 part by weight of stearic acid (NOF Corp., Beads Stearic Acid Tsubaki) Lubricant b: 0.3 parts by mass of stearylamide (Amide AP-1, manufactured by Mitsubishi Chemical Corporation) Lubricant c: Liquid paraffin (Kaneda Co., Ltd., Hi-Cold K-230) 1 part by weight Release agent: 0.5 parts by weight of fatty acid, fatty acid ester, amine, and wetting agent mixture (MoldWiz INT-21G, manufactured by Tomoe Engineering Co., Ltd.) Antioxidant: 0.5 parts by mass of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine (Naugard #445, manufactured by Addivant) Crosslinking agent: 0.5 parts by weight of hexamethylenediamine carbamate (Diak#1, manufactured by DuPont) Crosslinking accelerator: 1.0 part by weight of a synthetic mixture of active amine and retarder (LANXESS XLA-60)

[0106] The kneaded rubber composition was cut into a sheet having a thickness of 2.4 mm, and then heated and pressed at 170°C and a pressure of 10 MPa for 20 minutes using a press vulcanizer. Then, the rubber composition was heated in a gear oven at 170°C for 4 hours to obtain a crosslinked product of the rubber composition.

[0107] (Water resistance evaluation) In accordance with the "immersion test" of JIS K6258:2016, the cross-linked material was subjected to an immersion test in distilled water (80°C, 72 hours), and the volume change rate of the cross-linked material before and after the test was calculated based on the following formula. Volume change rate (%) = (volume after test - volume before test) / volume before test x 100 The results are shown in Tables 1 and 2. The smaller the volume change rate, the more excellent the water resistance.

[0108] (Measurement of tensile strength at break) The tensile strength at break Tb of the crosslinked product was measured according to JIS K6251: 2017. The results are shown in Tables 1 and 2.

[0109] [Table 1]

[0110] [Table 2]

[0111] The following evaluations of toluene insoluble matter, flex fatigue resistance, and copper damage resistance were also carried out for Examples 1 to 13. The results are shown in Tables 3 and 4.

[0112] (Measurement of toluene insolubles) 1 g of acrylic rubber was precisely weighed and dissolved in 100 mL of toluene at 25°C for 48 hours, and then the solution was transferred to a 250 mL centrifuge tube whose mass (referred to as X(g)) had been measured in advance. The solution was then centrifuged at 10°C, 8500 rpm, and 60 minutes using an angle rotor with a maximum centrifugal radius of 13.8 cm, and the non-precipitate was removed by decantation. The precipitate in the centrifuge tube was dried in a vacuum dryer at 70°C for 24 hours, and the mass of the centrifuge tube after drying (referred to as Y(g)) was measured. The toluene insolubles were calculated from the measured X and Y using the following formula. Toluene insolubles (mass%) = (YX) x 100 The smaller the toluene insoluble content, the more preferable.

[0113] (Evaluation of flex fatigue resistance) According to JIS K6260:2010, the number of times the crosslinked material was bent until a 0.5 mm crack appeared in the crosslinked material was measured in a 100°C environment. The number of times the crosslinked material was bent was the average value of the results of performing the same measurement on five samples. The higher the number of times the crosslinked material was bent, the better the resistance to bending fatigue.

[0114] (Evaluation of copper damage resistance) The cross-linked material molded into a No. 3 dumbbell shape was used as the test piece. 5 g of a slurry made by mixing engine oil (Mobil 15W-30 manufactured by EMG Lubricants LLC) and copper powder (CE-1110 manufactured by Fukuda Metal Foil and Powder Co., Ltd.) in a ratio of engine oil / copper powder = 3 / 1 (mass ratio) was applied with a brush so as to completely cover the area between the marks of the test piece, and the test piece was dried at room temperature for 12 hours. Next, a copper damage resistance test was performed by heating the test piece in a gear oven at 150 ° C for 500 hours. After that, the copper paste was peeled off from the test piece using a spatula, and the elongation of the test piece was measured according to JIS K6251:2010. The change in elongation (%) before and after the test was calculated based on the following formula. Elongation change rate (%) = (elongation after test - elongation before test) / elongation before test x 100 The smaller the absolute value of the elongation change rate, the better the copper damage resistance.

[0115] [Table 3]

[0116] [Table 4]

Claims

1. Contains acrylic rubber and a nonionic emulsifier, A rubber composition, in which more than 0 mass % and 50 mass % or less of the total mass of the nonionic emulsifier is fixed to the acrylic rubber.

2. The rubber composition according to claim 1, wherein a total mass of the nonionic emulsifier is 5 parts by mass or less per 100 parts by mass of a total mass of the acrylic rubber.

3. 2. The rubber composition according to claim 1, wherein the acrylic rubber contains at least one monomer unit selected from the group consisting of an alkyl acrylate, an alkyl methacrylate, and an alkoxyalkyl acrylate.

4. The rubber composition according to any one of claims 1 to 3, further comprising a crosslinking agent.

5. A crosslinked product of the rubber composition according to claim 4.

6. A step of polymerizing an acrylic monomer in the presence of a nonionic emulsifier to obtain a latex of an acrylic polymer; and coagulating and washing the acrylic polymer to obtain an acrylic rubber. The method for producing an acrylic rubber, wherein more than 0% by mass and 40% by mass or less of the total mass of the nonionic emulsifier in the latex is fixed to the acrylic polymer.

7. The method for producing an acrylic rubber according to claim 6, wherein a total mass of the nonionic emulsifier in the latex is 6 parts by mass or less per 100 parts by mass of a total mass of the acrylic polymer.

8. The method for producing an acrylic rubber according to claim 6 or 7, wherein the acrylic polymer contains at least one monomer unit selected from the group consisting of an alkyl acrylate, an alkyl methacrylate, and an alkoxyalkyl acrylate.

Citation Information

Patent Citations

  • Acrylic rubber composition

    JP2011006509A

  • Method for producing acrylic rubber, acrylic rubber, acrylic rubber composition, vulcanized substance thereof, and application for vulcanized substance

    WO2019078167A1

  • Acrylic rubber, rubber composition and crosslinked product thereof, rubber hose, and sealing component

    WO2021075128A1